Synthesis And Characterizations Of Various Metal-based Halloysite Nanocomposites For The Photo-degradation Of Liquid Epoxidized Natural Rubber - Saad, Abdullahi Shehu (2024)
In this research, various metal oxides (CuO, NiO, Co3O4, CrO and ZnO) based supported HNT photocatalysts were synthesized via wet impregnation of various metal salts (Cu(NO3)2.3H2O, NiSO4.6H2O, Ni(NO3)2.6H2O, Co(NO3)2.6H2O, Cr(NO3)3.9H2O, and Zn(NO3)2.6H2O) on HNT, followed by subsequent calcination techniques. HNT and photocatalysts were characterized by FTIR, XRD, AAS, SEM/EDX, BET, UV–Vis (DRS), and PL techniques and results confirmed the successful formation of photocatalysts (CuO, NiO, Co3O4, CrO and ZnO) supported HNT. The photocatalysts were subsequently employed to degrade LENR in the presence of UV irradiation. The photodegradation of LENR into shorter chains using metal oxide-supported catalysts is an alternative method which is efficient compared to the use of chemicals. It is significant for polymer industries due to its ability to produce low molecular weight components that can be used as raw materials. When compared to pristine LENR, the functional groups of degraded LENR exhibited some changes. GPC analysis reveals that the Mw of the degraded LENR was dramatically reduced, leading to the possibility of more chain scission. Thus, it can be established that the photocatalytic degradation of LENR is effective in the presence of photocatalysts. The Mw of LENR decreases after UV light exposure but increases with Ni2+-HNT catalyst. The Mw of 3H D-LENR(NiO-HNTs) reduced significantly from 25,732 for pristine LENR to 2.344 g/mol when calcined NiO-HNT was used for 3 hours of degradation. However, longer degradation times resulted in the crosslinking of short unstable chains formed.